The Importance of Reskilling and Upskilling for Employees - Mahdia, Asrini (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Reskilling and upskilling for employees is an important key in increasing competitiveness and global economic growth. This research explores the relationship between reskilling/upskilling initiatives and labor market needs through case studies in several countries. Findings from the case study highlight the importance of balancing training programs with evolving skills needs, facilitating early job placement and career advancement. However, the limitations of this study underscore the need for broader research, including organizational and peer impact, cost-time effectiveness, and the efficacy of reskilling/upskilling methodologies, especially in older employees. Additionally, future studies should explore the interaction between job crafting and reskilling/upskilling to identify effective learning strategies and overcome the challenges faced.